Ischemic Stroke in a Child with Sickle Cell Anemia, Patent Foramen Ovale and Moya-Moya Syndrome: The Challenges of Implementing a Secondary Prevention Strategy - Oliveira, Ednaldo França de; Machado, Michel Ferreira (Brazilian Journal of Case Reports, 2025)
Strokes, traditionally regarded as conditions affecting adults, can also occur in the pediatric population, where their rarity often delays diagnosis. This report describes the case of a seven-year-old boy with sickle cell anemia who was admitted with left-sided motor deficits. The patient had been febrile and recumbent the previous day. Laboratory tests revealed severe anemia (hemoglobin 6.7 g/dL). During hospitalization, a transthoracic echocardiogram identified a patent foramen ovale (PFO) with left-to-right atrial flow and dilation of the left heart chambers. Brain imaging revealed lesions in the vascular border zones, while cerebral angiography confirmed severe stenosis in the internal carotid artery and a Moyamoya pattern. Following an etiological investigation, the symptoms were attributed to an ischemic stroke. Empirical antimicrobial therapy, blood transfusions, and antiplatelet therapy were initiated. Two potential mechanisms for the stroke were identified: PFO and Moya-Moya syndrome (MMS). The coexistence of these rare conditions in a pediatric patient presented unique diagnostic and therapeutic challenges. MMS was considered the primary cause of the stroke due to characteristic imaging findings and the patient’s history of sickle cell anemia. This case highlights the complexities of managing pediatric strokes with dual pathologies and the importance of a multidisciplinary approach. It advances clinical understanding by demonstrating how PFO complicates secondary prevention in MMS and emphasizes the need for individualized treatment strategies and long-term follow-up to optimize outcomes.